Overview and Global Application History of Kaizen in Indonesia - Wardoyo, Stedi (Universitas Negeri Semarang, 2024)
This research aims to discover one of the forms of excellence, namely the application of Kaizen as a basic philosophy rooted in Japanese culture, which is one of the keys to the success of Japanese business and industry globally. This research method uses descriptive qualitative. The results of the study show that the application of Kaizen is perfect and suitable for long-term implementation. Numerous instruments are now available for use in production and various stages of the value chain with the goal of enhancing both product quality and operational efficiency. Nonetheless, kaizen can be viewed as one of the fundamental lean methods. One of the main components of Japanese management and a source of competitiveness is the implementation of Kaizen, or continuous improvement. Cost savings, less waste, and higher-quality products are all results of an efficient continuous improvement program. Kaizen is a technique that many businesses have embraced to improve production efficiency and attain business excellence, thanks to Japan's success. Even though kaizen has been widely adopted worldwide and has improved performance in numerous businesses, a lot of issues and challenges with its application may be discovered outside of Japan. The significance and severity of the many aspects that impact the Kaizen transfer process differ depending on the nation in which Kaizen is implemented. Therefore, despite its seeming simplicity, kaizen is a complex process that must be tailored to the environment's unique characteristics while taking into account a wide range of influencing elements.